Application Status of the Barkhausen Effect in Nondestructive Testing - Yuan Huijuan; Zhang Enjing; Li Hongmei; Fu Jian; Yang Ying Ying; Zou Ying; Hu Dandan (Universitas Ahmad Dahlan, 2014)
Change of internal structure or internal defect in ferromagnetic materials can produce change in Barkhausen noise, and by using Barkhausen noise signal measurement, the quality and internal defects of the material can be judged. The nondestructive testing technology is based on the Barkhausen effect, it gets the attention because of its advantages, such as rapid, non-destructive, mensurable, mainly used to detect stress, hardness, grain size, grinding burn etc.. The research status of Barkhausen effect in nondestructive testing was reviewed. Its application situation was investigated that the nondestructive testing technology based on the Barkhausen effect on stress, hardness, grain size, grinding burn detection etc., and the relationship between the MBN signals and stress, hardness, grain size, grinding burn were showed.